Crip Heroine or Mainstream Mock? - Negotiating the Performances of Lady Gaga - Lise Dilling-Hansen (The Royal Danish Library, 2015)
Since rumors about Lady Gaga's undefinable sex - and later sexuality and gender - began to spread, queer issues have been a central part of the artist's performative work. Through Gaga's social work, the norm-deviating body has become a central element too. This has led a whole generation of fans to frame Gaga as a queer hero, helping them coming out, and as a crip idol who, with her body as an activist tool, mobilizes hundreds of other bodies to participate in a bodily democratizing campaign aiming at higher self-esteem. Building on data collected in online media sites, this article investigates how the performances of Lady Gaga place her as a heroine to some, but at the same time produce heavy skepticism and criticism of the artist's intentions.